Tropical forests stand recovery 30-year after selectively logged in peninsular malaysia - Richard, Aldrich; Mohamad Kassim, Mohamad Roslan; Kudus, Kamziah Abd; Nazre Saleh, Mohd (Universiti Putra Malaysia, 2023)
This article analysed the 25–30 years of growth of dipterocarps forests that were logged under the Selective Management System (SMS) at three sites in Peninsular Malaysia to understand how management regimes affected forest stem density and basal area. The management regimes were (1) unlogged, (2) moderately logged forests that logged all dipterocarps ≥ 65 cm diameter at breast height (dbh) and all non-dipterocarps ≥ 60 cm dbh, and (3) intensely logged forests that logged all dipterocarps ≥ 50 cm dbh and non-dipterocarps ≥ 45 cm dbh. The intensely logged regime is similar to the SMS practices in Peninsular Malaysia. This result showed that one-year post-logging, there was no difference in the total stem density and basal area between forests logged according to the two management regimes. Forest stem density decreased over time in all management regimes, significantly greater in unlogged forests (-15.1 stems/ha/yr, confidence interval (CI): -16.9 to -13.3). This decline in stem density reflected that mortality exceeded recruitment in all management regimes. Despite the consistent decline of forest stem density, the basal area increased over time, and the rate of increase in the intensely logged forest (0.22 m2 /ha/yr, CI: 0.19 to 0.25) was significantly greater than the other management regimes. Our study showed that 30 years post-logging, the effect of selective logging remained evident. Both logged forest stem density and the basal area did not recover to that of unlogged forests, indicating the importance of enrichment planting and extending the cutting cycles beyond 30 years for the sustainability of dipterocarps forests.